A Foresight on Smell Detector toward Durian Fruit in Malaysia - Muhammad Ammar Shafi; Sapon, Siti Nor Aisyah; Ahmad, Nurazwa (Research in Management of Technology and Business, 2023)
The Recent advances in smell detector have led to the development of new applications; among them, the electronic nose has gained major interest and found successful application in many fields. An electronic nose is a device consisting of various smell detector with sensitivity to various chemical compounds. Durian fruit is known by admirers as the “King of Fruit” and characterized by its large size, strong smell, and hard thorn‐covered husk. Ripe durian has a unique taste with a strong aroma. Durian have characteristic smell which can give clues to the type of durian. In this study, we want to investigate the key drivers and to explore the future trends of smell detector toward durian fruit in Malaysia. The mixed approaches of qualitative and quantitative methods were used in the research. For the foresight of the application stretch and the use of smell detectors for durian fruit in Malaysia, various research methodologies such as remote sensing methods, STEEPV analysis, SPSS statistical analysis, impact uncertainty analysis and finally scenario building analysis have been implemented to identify the main future drivers and their impact on the future of corresponding smell detectors. The objectives of this research have been successfully achieved by identifying two top drivers and four alternative future trends that show how the need for the detection of the specific smells and structuring of the smell detector will impact and shape the way of life in the future